Maturação, armazenamento e metabolismo da parede celular de diferentes variedades de melões - Pontes, Felipe Moura (Universidade Federal Rural do Semi-Árido, 2017)
Fruit flesh firmness has a close relation with the cell wall compounds, thus, a higher knowledge about the metabolism of such compounds is indispensable to aspects related to flesh texture change. In the case of melon, the study of flesh firmness is facilitated since it has a great variability, whose amplitude allows a better observation of differences between biochemistry phenomena of cell wall. For that reason, the present work aimed to evaluate the comportment of the varieties acidulus (access 16), momordica (access 2), inodorus (cv. Iracema) and cantalupensis (cv. Olympic), related to maturation and storage of the fruits. Therefore, two experiments were installed. At first one, about maturation, fruits were obtained from determined harvest times by flower anthesis, and a completely randomized design for each mentioned variety was set. In the second one, melons of acidulus, momordica and inodorus varieties were stored in cooler with humidity control (9±1 °C e 85±5%), and evaluated from fruit samples randomLy picked, on a determined time according to each variety durability. For both experiments, fruits were evaluated to physical and chemical characteristics; to the pectinases activity of pectin methylestarese, poligalacturonase and betagalactosidase; and pectin content in three solubilization levels: water soluble, chelate soluble and sodium carbonate soluble. The adequate harvest day for each melon was, 35 days after anthesis for cv. Iracema, 30 days for cv. Olympic, 30 days for access 16 and 20 days for access 2. During maturation, it was observed high flesh firmness of access 16, when compared to remain fruits evaluated, due to its low betagalactosidase activity, as well as its upkeep of chelate and sodium carbonate pectin. Access 2 showed a high decrease in firmness, followed by the tissue cracking at the end of maturation; such an event was consecutive of the water soluble pectin increase and decrease of the chelate and sodium carbonate soluble pectins, with a raise of all pectinases at the maturation ending. Access 16 and the yellow melon (cv. Iracema) has storage potential of 30 days, in refrigerated storage. Access 2, at same conditions, had durability of 10 days. The firmness loss of all studied melons types has been associated to the Betagalactosidase enzyme activity, and to the reduction of the chelate and sodium carbonate pectin fractions. Access 16 had high conservation, keeping flesh firmness until 32 days, with high pectin levels due to low pectinase levels. The access 2 fruits showed a high decrease on flesh firmness, what deteriorated the inner appearance of the fruit. Both pectinases activities as pectin dissolution contributed to the occurred
Maturation, storage and cell wall metabolism of different melon varieties
Keywords: Acidulus; Momordica; Firmeza; Conservação; Pectinases; Cucumis melo; Acidulus; Momordica; Firmness; Conservation; Pectinase; Cucumis melo; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA